If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + 2(8x + -7) = -16 Reorder the terms: -2 + 2(-7 + 8x) = -16 -2 + (-7 * 2 + 8x * 2) = -16 -2 + (-14 + 16x) = -16 Combine like terms: -2 + -14 = -16 -16 + 16x = -16 Add '16' to each side of the equation. -16 + 16 + 16x = -16 + 16 Combine like terms: -16 + 16 = 0 0 + 16x = -16 + 16 16x = -16 + 16 Combine like terms: -16 + 16 = 0 16x = 0 Solving 16x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '16'. x = 0 Simplifying x = 0
| 4(-p)=4p+4 | | 21=5-(2a-1) | | -m-(-4)=-7 | | 4y+9+3y=8+5y-27 | | 6x^2+11x-6=0 | | -2(y+1)=-9y+12 | | 5(2*-7)-3=5(x-2)+17 | | 6+4x+11=6x-8+3x+5 | | 9(x+4)= | | 4x-8-2x=2x+4 | | 5x-9y=24 | | 5x-10=11x | | (7rs^5)(-3r^3s^4)= | | 4x^2-5x-57=0 | | 27a^3-1000=0 | | 4m+4=4m | | 4z+8-z+3=2z+23 | | 4x^2+1=2x+3 | | 15x-188=5x-8 | | x=3x+3x*x | | 10y-9xy= | | -20+10-18= | | 17=2-(6+n) | | 6-4(n+3)=8(2n+4)-n | | -2(n+7)-6n=-20-7n | | 70-(23-9)= | | 5(w-5)-7w=-31 | | 2x(x-7)=0 | | 11-2x=1-7x | | 2x+1+x/2=2x/3+3+2x/3 | | 5(1+v)+2=8(v-4) | | 7+2(9-3)=9 |